Testing the dimensionality of place attachment and its relationships with place satisfaction and pro-environmental behaviours: A structural equation modelling approach - Ramkissoon, Haywantee; Smith, L.; Weiler, B. (Pergamon, 2013)
Drawing on literature from environmental psychology, the present study examined place attachment as a second-order factor and investigated its relationships with place satisfaction and visitors’ low and high effort pro-environmental behavioural intentions. Confirmatory factor analysis and structural equation modelling were used to test a model using a sample of 452 visitors at the Dandenong Ranges National Park, in Australia. Results supported the four-dimensional second-order factor of place attachment and indicated (a) positive and significant effects of place attachment on both low and high effort proenvironmental behavioural intentions of park visitors, (b) a significant and positive influence of place attachment on place satisfaction, (c) a significant and positive effect of place satisfaction on low effort pro-environmental behavioural intentions, and (d) a negative and significant influence of place satisfaction on high effort pro-environmental behavioural intentions. The main theoretical contribution relates to the inclusion of the four dimensions of place attachment in a single model. Findings are discussed with respect to their applied and theoretical relevance.